Core-shell type catalyst as well as preparation method and application thereof
By using core-shell catalysts in the acidic system, hexavalent uranium is efficiently reduced to tetravalent uranium, which solves the problems of low catalyst reaction efficiency and low hydrazine utilization in the prior art, and achieves the preparation of tetravalent uranium with high conversion and high yield.
Patent Information
- Application Number
- CN202411722892.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the catalyst reaction efficiency and low hydrazine utilization rate lead to low conversion of hexavalent uranium, making it difficult to efficiently prepare tetravalent uranium solutions.
Using core-shell catalysts, an eggshell catalyst is designed by mainly distributing the active component precious metal nanoparticles in the shell of the support in an acidic system to improve the conversion rate of hexavalent uranium and the utilization rate of hydrazine.
Under acidic conditions, the conversion rate of hexavalent uranium can reach 99%, the utilization rate of hydrazine is increased, the use of precious metals is reduced, the reaction activity is high, and the yield of tetravalent uranium is high.
Smart Images

Figure CN119633807A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a core-shell catalyst and a preparation method and application thereof, belonging to the field of catalysts. Background Art
[0002] Nuclear fuel reprocessing refers to the process of recovering uranium, plutonium and other valuable elements from used nuclear fuel. At present, nuclear fuel reprocessing plants at home and abroad mainly use the Purex process. The Purex process mainly uses the different extraction capabilities of tributyl phosphate (TBP) for uranium, plutonium and fission products to achieve their separation. In the uranium-plutonium separation stage, the extraction capacity of TBP for trivalent plutonium is very small, so uranium and plutonium are separated. However, plutonium is tetravalent in the front-end process, so a reducing agent must be added to reduce it to trivalent. Quadrivalent uranium (U(IV)) is a better reduction and stripping agent for tetravalent plutonium (Pu(IV)). It has the advantages of complete plutonium reduction and stripping, no impurities introduced into the system, and fast reaction rate, and is widely used. Therefore, the efficient preparation of quadrivalent uranium is of great significance in the purex process.
[0003] Using organic reducing agents such as hydrazine, formic acid, and formaldehyde, U(VI) can be reduced to U(IV) under the action of a catalyst. It has the advantages of mild reaction conditions and a simple preparation process. It is a very promising method for preparing U(VI). Li Bin et al. used platinum black as a catalyst to study the process conditions for the hydrazine reduction of U(VI) to U(IV) in a nitric acid system. When the uranium concentration was 0.9 mol / L, the HNO3 concentration was 0.8 mol / L, and the hydrazine concentration was 1 mol / L, the conversion rate of U(VI) could reach more than 90% at 60°C. (Nuclear Chemistry and Radiochemistry, 2013, 35, (1): 24-28). Boltoeva et al. investigated the particle size effect of Pt in the hydrazine reduction of U(VI) to U(IV) in a Pt / SiO2 catalyst in a H2SO4, HClO4, and HNO3 system. It was found that the U(VI) conversion rate increased with the increase of Pt particle size (Radiochemistry, 2007, 49, 603-606). Anan'ev et al. investigated the reaction performance of hydrazine and formic acid in the nitric acid system to reduce U(VI) to U(IV) (Radiochemistry, 2001, 43, 39-43). When hydrazine is used as the reducing agent, the reaction of U(VI) reduction is as shown in formula (1). However, in this reaction system, hydrazine nitrate may also self-decompose to produce NH4 +, as shown in formula (2). Since the diffusion rate of uranyl molecules is slow, while the diffusion rate of hydrazine molecules is fast, the U(VI) reduction reaction is more likely to occur on the outer surface of the catalyst, while the hydrazine decomposition reaction is more likely to occur inside the catalyst pores. The rates of different reactions can be adjusted by designing catalysts with non-uniform distribution of active components. The eggshell-type catalyst is used, so that the active components are mainly distributed on the surface of the carrier, which is expected to increase the U(VI) reaction activity and reduce the activity of the hydrazine decomposition reaction, and reduce the use of precious metals.
[0004] By preparing precious metal nanosols and utilizing the "binding" effect of colloidal particles on precious metal particles, the diffusion rate of precious metal particles in the carrier is significantly reduced, so that the nanoparticles are mainly distributed in the shell layer of the carrier, thereby constructing an eggshell-type catalyst.
[0005] N2H5 + + 3H + +2UO2 2+ → 2U 4+ + N2 + 4H2O (1)
[0006] 3N2H5 + + H + → N2 + 4NH4 + (2)
[0007] At present, some patents have been applied for the preparation of tetravalent uranium solution. The following are several reported patents for detailed description:
[0008] The Chinese patent CN201110097474 is publicly named: A method for preparing a tetravalent uranium solution. The patent reports the use of an organic reducing agent (hydrazine or carboxylic acid and its derivatives) to reduce U(VI) to prepare a U(IV) solution under the action of a Pt catalyst. The catalyst involved in the patent is platinum black, and direct Pt nanoparticles are used as catalysts. The dispersion of Pt is low and the catalytic efficiency is not high.
[0009] The Chinese patent CN201310743451 is publicly named: A device for preparing tetravalent uranium by electrolytic reduction. The patent reports an improved device for preparing tetravalent uranium by electrolytic reduction, which mainly solves the problem of low U(VI) conversion rate in a diaphragmless electrolysis device. In actual production, the effectiveness of the device needs further verification.
[0010] The Chinese patent CN201910865308 is publicly named: A catalyst, method and application for removing hexavalent uranium by visible light catalytic reduction. The patent reports that the use of ZnFe2O4 catalyst can reduce U(VI) in wastewater to U(IV) under light conditions and generate precipitation. Thereby removing U(VI) ions from the wastewater. The catalyst involved in the patent is ZnFe2O4, which uses a photocatalytic reduction method to remove U(VI) ions.
[0011] At present, due to the problems of low catalyst reaction efficiency and low hydrazine utilization rate, it is urgent to develop an efficient catalyst to improve the U(VI) conversion rate and hydrazine utilization rate. Summary of the invention
[0012] In view of the problems of low reaction efficiency and low hydrazine utilization rate in the above-mentioned process of preparing tetravalent uranium, a method for preparing an eggshell-type catalyst for catalytic reduction of hexavalent uranium to prepare tetravalent uranium is provided, in which tetravalent uranium is prepared by catalytic reduction of hexavalent uranium with a high-efficiency catalyst in an acidic system.
[0013] According to one aspect of the present application, a core-shell catalyst is provided, wherein the core-shell catalyst has a carrier as a core and an active component as a shell;
[0014] The active component is a noble metal, selected from at least one of Pt, Ir, Rh, Ru, and Pd;
[0015] In the core-shell catalyst, the mass content of active components is 0.1-5%.
[0016] The carrier is selected from at least one of SiO2, Al2O3, and TiO2.
[0017] According to another aspect of the present application, a method for preparing the core-shell catalyst is provided, comprising the following steps:
[0018] (1) mixing an alcohol aqueous solution A containing an active component precursor with an alcohol aqueous solution B containing an alkali, heating and stirring under an inert gas atmosphere to obtain an active component sol;
[0019] (2) The alcohol aqueous solution C containing the carrier is mixed with the active component sol, stirred, filtered, dried, and calcined to obtain the core-shell catalyst.
[0020] The alcohol is selected from at least one of ethylene glycol, propylene glycol and glycerol;
[0021] The mass ratio of the alcohol to water is 3 to 50:1.
[0022] The active component precursor is selected from at least one of nitrates and chlorides of Pt, Ir, Rh, Ru, and Pd;
[0023] The alkali is selected from at least one of sodium hydroxide and potassium hydroxide;
[0024] In the alcohol aqueous solution A containing the active component precursor, the concentration of the active component precursor is 0.01 to 0.04 g / ml;
[0025] The alcohol aqueous solution B containing alkali has a concentration of 0.002 to 0.01 g / ml;
[0026] The volume ratio of the alcohol aqueous solution A containing the active component precursor to the alcohol aqueous solution B containing the alkali is 1:1-3;
[0027] The heating temperature is 150-200°C;
[0028] The heating time is 2 to 12 hours;
[0029] The inert gas atmosphere includes at least one of nitrogen, helium and argon.
[0030] In the alcohol aqueous solution C containing a carrier, the content of the carrier is 0.005-0.1 g / ml;
[0031] The volume ratio of the active component sol to the alcohol aqueous solution C containing the carrier is 0.0005-0.4:1;
[0032] The stirring temperature is 60-90°C;
[0033] The stirring time is 2 to 12 hours;
[0034] The drying temperature is 60-120°C;
[0035] The drying time is 1 to 24 hours;
[0036] The calcination temperature is 200-500°C;
[0037] The calcination time is 2 to 8 hours.
[0038] According to another aspect of the present application, a method for preparing tetravalent uranium by catalytic reduction of hexavalent uranium in an acidic system is provided, wherein an acidic solution, a catalyst, a reducing agent and a raw material containing uranyl ions are mixed in a reactor to obtain a mixed solution, and the mixture is reacted to obtain a product containing tetravalent uranium;
[0039] The uranium in the uranyl ions is hexavalent uranium;
[0040] The catalyst is the core-shell catalyst mentioned above.
[0041] The reactor is a tank reactor or a fixed bed reactor.
[0042] The acidic solution is selected from at least one of nitric acid, sulfuric acid, and perchloric acid;
[0043] The reducing agent is selected from at least one of hydrazine, formic acid and formaldehyde;
[0044] The raw material is selected from at least one of uranyl nitrate, uranyl sulfate and uranyl perchlorate.
[0045] The concentration of the acidic solution is 0.5 to 1.0 mol / L, measured in terms of hydrogen ion concentration;
[0046] In the mixed solution, the concentration of the reducing agent is 0.5 to 2.0 mol / L;
[0047] In the mixed solution, the raw material concentration is 100 to 300 g / L, measured by uranium ion mass;
[0048] Optionally, in the mixed solution, the molar ratio of the acidic solution, the reducing agent, and the raw material is 1:0.3-3.0:0.5-1.2;
[0049] The mass ratio of the raw material to the catalyst is 100-300:1.
[0050] The reaction temperature is 15 to 60°C;
[0051] The reaction time is 0.5 to 6 hours;
[0052] The reaction pressure is normal pressure.
[0053] The beneficial effects of this application include:
[0054] 1 ) The eggshell-type catalyst provided in the present application can improve the conversion rate of hexavalent uranium and the utilization rate of hydrazine, and reduce the usage of precious metals.
[0055] 2) The eggshell-type catalyst provided in the present application can reduce hexavalent uranium to a tetravalent uranium solution using a liquid phase reducing agent under acidic conditions. In a stirred tank reactor, the conversion rate of hexavalent uranium can reach 99% within 0.5 h, and the reaction has high stability in a fixed reactor.
[0056] 3) The method for preparing tetravalent uranium by catalytic reduction of hexavalent uranium with an eggshell-type catalyst provided in the present application has the advantages of low usage of precious metals, high reaction activity, mild reaction conditions, and high yield of tetravalent uranium. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a schematic diagram of the preparation of an eggshell-type catalyst according to Example 1 of the present application. DETAILED DESCRIPTION
[0058] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0059] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0060] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0061] The conversion rate in the examples of this application is calculated as follows:
[0062]
[0063] Example 1
[0064] according to Figure 1 The eggshell catalyst is prepared according to the process shown in the figure. The specific preparation process is as follows:
[0065] 1) Preparation of active component nanosol
[0066] 2g H2PtCl6·6H2O was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution A, wherein the mass ratio of ethylene glycol to water was 50:1; 0.1g sodium hydroxide was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution B, wherein the mass ratio of ethylene glycol to water was 50:1. After A and B were evenly mixed, they were transferred to a 160°C oil bath and stirred for 6 hours under argon atmosphere protection to obtain a Pt sol with a Pt mass concentration of 7.5mg / ml.
[0067] 2) Preparation of eggshell catalyst
[0068] 1g SiO2 carrier was dispersed in 100mL of a mixture of glycol and water c to form a suspension D, wherein the mass ratio of ethylene glycol to water was 50:1; 2.05ml of the Pt sol prepared above was added dropwise to the carrier suspension under vigorous stirring, and stirred at 80°C for 6h. Then, it was filtered, dried in an oven at 80°C for 12h, and then calcined in a muffle furnace at 400°C for 2h to obtain an eggshell-type catalyst, which was labeled as 3% Pt / SiO2-eggshell.
[0069] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, hydrazine nitrate concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0070] Example 2
[0071] 1) Preparation of active component nanosol
[0072] 1g H2IrCl6·6H2O was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution A, wherein the mass ratio of ethylene glycol to water was 3:1; 0.1g potassium hydroxide was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution B, wherein the mass ratio of ethylene glycol to water was 3:1. After A and B were mixed evenly, they were transferred to a 150℃ oil bath and stirred for 12h under argon atmosphere protection to obtain Ir sol with an Ir mass concentration of 3.7mg / ml.
[0073] 2) Preparation of eggshell catalyst
[0074] 1g of Al2O3 carrier was dispersed in 100mL of a mixture of glycol and water c to form a suspension D, wherein the mass ratio of ethylene glycol to water was 3:1; 4.14ml of the above-prepared Ir sol was added dropwise to the carrier suspension under vigorous stirring, and stirred at 90°C for 2h. Then, it was filtered, dried in an oven at 60°C for 12h, and then calcined in a muffle furnace at 200°C for 8h to obtain an eggshell-type catalyst, which was marked as 3% Ir / Al2O3-eggshell.
[0075] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, hydrazine nitrate concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0076] Example 3
[0077] 1) Preparation of active component nanosol
[0078] 1g RhCl3·3H2O was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution A, wherein the mass ratio of ethylene glycol to water was 30:1; 1g sodium hydroxide was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution B, wherein the mass ratio of ethylene glycol to water was 30:1. A and B were mixed evenly and transferred to a 200℃ oil bath, and stirred for 2h under nitrogen atmosphere protection to obtain Rh sol, with a Rh mass concentration of 4.0mg / ml.
[0079] 2) Preparation of eggshell catalyst
[0080] 10g TiO2 carrier was dispersed in 100mL of a mixture of glycol and water c to form a suspension D, wherein the mass ratio of ethylene glycol to water was 30:1; 39.56ml of the above-prepared Rh sol was added dropwise to the carrier suspension under vigorous stirring, and stirred at 60°C for 12h. Then, it was filtered, dried in an oven at 120°C for 4h, and then calcined in a muffle furnace at 500°C for 2h to obtain an eggshell-type catalyst, which was labeled as 3% Rh / TiO2-eggshell.
[0081] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, hydrazine nitrate concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0082] Example 4
[0083] 1) Preparation of active component nanosol
[0084] 2g of RuCl3·3H2O was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution A, wherein the mass ratio of ethylene glycol to water was 40:1; 0.5g of sodium hydroxide was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution B, wherein the mass ratio of ethylene glycol to water was 40:1. After A and B were mixed evenly, they were transferred to an oil bath at 180°C and stirred for 6 hours under argon atmosphere protection to obtain Rh sol with a Rh mass concentration of 9.7mg / ml.
[0085] 2) Preparation of eggshell catalyst
[0086] 5g of SiO2 carrier was dispersed in 100mL of a mixture of glycol and water c to form a suspension D, wherein the mass ratio of ethylene glycol to water was 40:1; 7.93ml of the Ru sol prepared above was added dropwise to the carrier suspension under vigorous stirring, and stirred at 80°C for 6h. Then, it was filtered, dried in an oven at 110°C for 8h, and then calcined in a muffle furnace at 400°C for 4h to obtain an eggshell-type catalyst, which was labeled as 3% Ru / SiO2-eggshell.
[0087] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, hydrazine nitrate concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0088] Example 5
[0089] 1) Preparation of active component nanosol
[0090] 1g PdCl2 was dissolved in 100mL of a mixture of ethylene glycol and water to obtain solution A, wherein the mass ratio of ethylene glycol to water was 5:1; 0.1g sodium hydroxide was dissolved in 50ml of a mixture of ethylene glycol and water to obtain solution B, wherein the mass ratio of ethylene glycol to water was 5:1. A and B were mixed evenly and transferred to an oil bath at 180°C, and stirred for 4h under argon atmosphere protection to obtain Pd sol, with a Pd mass concentration of 4.0mg / ml.
[0091] 2) Preparation of eggshell catalyst
[0092] 5g of SiO2 carrier was dispersed in 100mL of a mixture of glycol and water c to form a suspension D, wherein the mass ratio of ethylene glycol to water was 5:1; 5.15ml of the Pd sol prepared above was added dropwise to the carrier suspension under vigorous stirring, and stirred at 70°C for 6h. Then, it was filtered, dried in an oven at 110°C for 8h, and then calcined in a muffle furnace at 400°C for 4h to obtain an eggshell-type catalyst, which was labeled as 3% Pd / SiO2-eggshell.
[0093] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, hydrazine nitrate concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0094] Example 6
[0095] 1) Preparation of active component nanosol
[0096] 2g H2PtCl6·6H2O was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution A, wherein the mass ratio of ethylene glycol to water was 50:1; 0.1g sodium hydroxide was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution B, wherein the mass ratio of ethylene glycol to water was 50:1. After A and B were evenly mixed, they were transferred to a 160°C oil bath and stirred for 6 hours under argon atmosphere protection to obtain a Pt sol with a Pt mass concentration of 7.5mg / ml.
[0097] 2) Preparation of eggshell catalyst
[0098] 1g of SiO2 carrier was dispersed in 100mL of a mixture of glycol and water c to form a suspension D, wherein the mass ratio of ethylene glycol to water was 50:1; 0.06ml of the Pt sol prepared above was added dropwise to the carrier suspension under vigorous stirring, and stirred at 80°C for 6h. Then, it was filtered, dried in an oven at 80°C for 12h, and then calcined in a muffle furnace at 400°C for 2h to obtain an eggshell-type catalyst, which was marked as 0.1% Pt / SiO2-eggshell.
[0099] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, hydrazine nitrate concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0100] Example 7
[0101] 1) Preparation of active component nanosol
[0102] 2g H2PtCl6·6H2O was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution A, wherein the mass ratio of ethylene glycol to water was 50:1; 0.1g sodium hydroxide was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution B, wherein the mass ratio of ethylene glycol to water was 50:1. After A and B were evenly mixed, they were transferred to a 160°C oil bath and stirred for 6 hours under argon atmosphere protection to obtain a Pt sol with a Pt mass concentration of 7.5mg / ml.
[0103] 2) Preparation of eggshell catalyst
[0104] 1g SiO2 carrier was dispersed in 100mL of a mixture of glycol and water c to form a suspension D, wherein the mass ratio of ethylene glycol to water was 50:1; 0.67ml of the Pt sol prepared above was added dropwise to the carrier suspension under vigorous stirring, and stirred at 80°C for 6h. Then, it was filtered, dried in an oven at 80°C for 12h, and then calcined in a muffle furnace at 400°C for 2h to obtain an eggshell-type catalyst, which was marked as 1% Pt / SiO2-eggshell.
[0105] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, hydrazine nitrate concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0106] Example 8
[0107] 1) Preparation of active component nanosol
[0108] 2g H2PtCl6·6H2O was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution A, wherein the mass ratio of ethylene glycol to water was 50:1; 0.1g sodium hydroxide was dissolved in 50mL of a mixture of ethylene glycol and water to obtain solution B, wherein the mass ratio of ethylene glycol to water was 50:1. After A and B were evenly mixed, they were transferred to a 160°C oil bath and stirred for 6 hours under argon atmosphere protection to obtain a Pt sol with a Pt mass concentration of 7.5mg / ml.
[0109] 2) Preparation of eggshell catalyst
[0110] 1g of SiO2 carrier was dispersed in 100mL of a mixture of glycol and water c to form a suspension D, wherein the mass ratio of ethylene glycol to water was 50:1; 3.49ml of the Pt sol prepared above was added dropwise to the carrier suspension under vigorous stirring, and stirred at 80°C for 6h. Then, it was filtered, dried in an oven at 80°C for 12h, and then calcined in a muffle furnace at 400°C for 2h to obtain an eggshell-type catalyst, which was labeled as 5% Pt / SiO2-eggshell.
[0111] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, hydrazine nitrate concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0112] Example 9
[0113] Take the 3% Pt / SiO2-eggshell catalyst prepared in Example 1.
[0114] The reaction conditions for the catalyst in the stirred tank were as follows: sulfuric acid concentration (in terms of hydrogen ion concentration) was 1.0 mol / L, uranyl (uranyl sulfate) ion concentration was 100 g / L, hydrazine sulfate concentration was 2.0 mol / L, temperature was 15°C, stirring rate was 800 rpm, pressure was normal pressure, catalyst dosage was 1.0 g, and reaction liquid was 25 mL. The reaction results are shown in Table 1.
[0115] Example 10
[0116] Take the 3% Pt / SiO2-eggshell catalyst prepared in Example 1.
[0117] The catalyst was used in the reaction conditions in the stirred tank: perchloric acid concentration (in terms of hydrogen ion concentration) was 0.5 mol / L, uranyl (uranyl perchlorate) ion concentration was 300 g / L, hydrazine perchlorate concentration was 0.5 mol / L, temperature was 60°C, stirring rate was 800 rpm, pressure was normal pressure, catalyst dosage was 1.0 g, and reaction liquid was 25 mL. The reaction results are shown in Table 1.
[0118] Embodiment 11
[0119] Take the 3% Pt / SiO2-eggshell catalyst prepared in Example 1.
[0120] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, formic acid concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0121] Example 12
[0122] Take the 3% Pt / SiO2-eggshell catalyst prepared in Example 1.
[0123] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, formaldehyde concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0124] Embodiment 13
[0125] Take the 3% Pt / SiO2-eggshell catalyst prepared in Example 1.
[0126] Reaction conditions in fixed bed: nitric acid concentration (in terms of hydrogen ion concentration) is 0.8 mol / L, uranyl (uranyl nitrate) ion concentration is 210 g / L, formaldehyde concentration is 1.0 mol / L, temperature is 25 °C, liquid space velocity is 0.3 h -1 , the pressure was normal pressure, the amount of catalyst was 20 g, and the flow rate of the reaction liquid was 0.2 ml / min. The reaction results are shown in Table 1.
[0127] Comparative Example 1
[0128] Take 5.0g of ordinary spherical SiO2 carrier, weigh 0.399g H2PtCl6·6H2O and dissolve it in 5ml deionized water to make a mixed solution. The molar concentration of Pt is 0.154mol / L. Add it dropwise to the SiO2 carrier and mix it evenly. Soak at room temperature for 12h, dry at 80℃ for 12h, and roast in air atmosphere at 300℃ for 4h. The mass content of Pt is 3%, which is recorded as 3Pt / SiO2 catalyst. Take 40ml of 0.5mol / L hydrazine hydrate, pour the roasted catalyst into it, and maintain it at 30℃ for 4h. Filter and wash the reduced catalyst, and dry it at 60℃ for use. Recorded as 3Pt / SiO2-uniform type.
[0129] The reaction conditions for the catalyst in the stirred tank were: nitric acid concentration (in terms of hydrogen ion concentration) of 0.8 mol / L, uranyl (uranyl nitrate) ion concentration of 210 g / L, hydrazine nitrate concentration of 1.0 mol / L, temperature of 60°C, stirring rate of 800 rpm, pressure of normal pressure, catalyst dosage of 1.0 g, and reaction liquid of 25 mL. The reaction results are shown in Table 1.
[0130] Example result analysis:
[0131] From the data analysis in Table 1, it can be seen that when the eggshell-type precious metal Pt or Ir or Rh or Ru or Pd-based catalyst obtained by first preparing the precious metal nanosol is used, when hydrazine nitrate, formic acid, formaldehyde, etc. are used as reducing agents under acidic conditions, the U(VI) conversion rate in the U(VI) to U(IV) reaction is higher than 90%.
[0132] In the 3Pt / SiO2-eggshell catalyst, when hydrazine nitrate is used as the reducing agent, the U(VI) conversion rate can reach 99%. Moreover, in the fixed bed reactor, the 3Pt / SiO2-eggshell catalyst also shows good reaction performance in the reduction of U(VI) to U(IV) by hydrazine nitrate, and the U(VI) conversion rate can reach 99%. However, the U(VI) conversion rate of the uniformly distributed catalyst obtained by using ordinary SiO2 is only 60% at 180min.
[0133] It is shown that the eggshell-type noble metal catalyst prepared by using the pretreated carrier has good performance in the reaction of U(VI) to U(IV) when hydrazine nitrate, formic acid, formaldehyde, etc. are used as reducing agents under acidic conditions.
[0134] Table 1 Reaction performance of catalytic reduction of hexavalent uranium to tetravalent uranium on different catalysts
[0135]
[0136]
[0137] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A core-shell catalyst, characterized in that The core-shell catalyst has a carrier as a core and an active component as a shell; The active component is a noble metal, selected from at least one of Pt, Ir, Rh, Ru, and Pd; In the core-shell catalyst, the mass content of active components is 0.1-5%.
2. The core-shell catalyst according to claim 1, characterized in that The carrier is selected from at least one of SiO2, Al2O3, and TiO2.
3. A method for preparing a core-shell catalyst according to any one of claims 1 or 2, characterized in that: The following steps are involved: (1) mixing an alcohol aqueous solution A containing an active component precursor with an alcohol aqueous solution B containing an alkali, heating and stirring under an inert gas atmosphere to obtain an active component sol; (2) The alcohol aqueous solution C containing the carrier is mixed with the active component sol, stirred, filtered, dried, and calcined to obtain the core-shell catalyst.
4. The preparation method according to claim 3, characterized in that: The alcohol is selected from at least one of ethylene glycol, propylene glycol and glycerol; The mass ratio of the alcohol to water is 3 to 50:
1.
5. The preparation method according to claim 3, characterized in that: The active component precursor is selected from at least one of nitrates and chlorides of Pt, Ir, Rh, Ru, and Pd; The alkali is selected from at least one of sodium hydroxide and potassium hydroxide; In the alcohol aqueous solution A containing the active component precursor, the concentration of the active component precursor is 0.01 to 0.04 g / ml; The alcohol aqueous solution B containing alkali has a concentration of 0.002 to 0.01 g / ml; The volume ratio of the alcohol aqueous solution A containing the active component precursor to the alcohol aqueous solution B containing the alkali is 1:1-3; The heating temperature is 150-200°C; The heating time is 2 to 12 hours; The inert gas atmosphere includes at least one of nitrogen, helium and argon.
6. The preparation method according to claim 3, characterized in that: In the alcohol aqueous solution C containing a carrier, the content of the carrier is 0.005-0.1 g / ml; The volume ratio of the active component sol to the alcohol aqueous solution C containing the carrier is 0.0005-0.4:1; The stirring temperature is 60-90°C; The stirring time is 2 to 12 hours; The drying temperature is 60-120°C; The drying time is 1 to 24 hours; The calcination temperature is 200-500°C; The calcination time is 2 to 8 hours.
7. A method for preparing tetravalent uranium by catalytic reduction of hexavalent uranium in an acidic system, characterized in that: In a reactor, an acidic solution, a catalyst, a reducing agent and a raw material containing uranyl ions are mixed to obtain a mixed solution, and the mixture is reacted to obtain a product containing tetravalent uranium; The uranium in the uranyl ions is hexavalent uranium; The catalyst is a core-shell catalyst according to any one of claims 1 or 2.
8. The method according to claim 7, characterized in that The acidic solution is selected from at least one of nitric acid, sulfuric acid, and perchloric acid; The reducing agent is selected from at least one of hydrazine, formic acid and formaldehyde; The raw material is selected from at least one of uranyl nitrate, uranyl sulfate and uranyl perchlorate.
9. The method according to claim 7, characterized in that: The concentration of the acidic solution is 0.5 to 1.0 mol / L, measured in terms of hydrogen ion concentration; In the mixed solution, the concentration of the reducing agent is 0.5 to 2.0 mol / L; In the mixed solution, the raw material concentration is 100 to 300 g / L, measured by uranium ion mass; Preferably, in the mixed solution, the molar ratio of the acidic solution, the reducing agent, and the raw material is 1:0.3-3.0:0.5-1.2; The mass ratio of the raw material to the catalyst is 100-300:
1.
10. The method according to claim 7, characterized in that The reaction temperature is 15 to 60°C; The reaction time is 0.5 to 6 hours; The reaction pressure is normal pressure.
Citation Information
Patent Citations
Method for preparing uranous solution
CN102249331A
Device for preparing tetravalent uranium by electrolytic reduction
CN103695956A
Catalyst and method for removing hexavalent uranium through visible light catalytic reduction, and applications of method
CN110639529A
Cited By
Noble metal catalyst with core-shell structure as well as preparation method and application of noble metal catalyst
CN120754844A